2020
DOI: 10.1016/j.bmcl.2020.127571
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel orally bioavailable NLRP3 inflammasome inhibitor

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Recently published structure-activity relationships concerning diarylsulfonylurea-based NLRP3 inhibitors revealed the intact western indacene moiety of CRID3/MCC950 to be crucial for biological activity, and hence for target binding. On the other hand, structural alterations on the eastern sulfonamide part were better tolerated (Hill et al, 2017(Hill et al, , 2020bAgarwal et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Recently published structure-activity relationships concerning diarylsulfonylurea-based NLRP3 inhibitors revealed the intact western indacene moiety of CRID3/MCC950 to be crucial for biological activity, and hence for target binding. On the other hand, structural alterations on the eastern sulfonamide part were better tolerated (Hill et al, 2017(Hill et al, , 2020bAgarwal et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…(2019) proposed that mitochondrial transporters ABCb7 and ABCb10 are the pharmacological targets of CP-453773; although this hypothesis has been proven incorrect, they found that undifferentiated THP1 cells can serve as a reliable and simplified model for investigating NLRP3 inflammasomes ( Guzova et al., 2019 ). MCC950 was found to increase serum liver enzyme levels in a phase II clinical trial in rheumatoid arthritis; hence, it was not further developed ( Agarwal, Pethani, et al., 2020 ). Abdullaha et al.…”
Section: Specific Inhibitors Of Nlrp3 Inflammasomementioning
confidence: 99%
“… Agarwal et al. (2020) reported that thiazolo-alkenyl sulfonylurea derivative 7 inhibited the activation of NLRP3 by inhibiting ASC oligomerisation ( Agarwal, Pethani, et al., 2020 ).…”
Section: Specific Inhibitors Of Nlrp3 Inflammasomementioning
confidence: 99%
See 2 more Smart Citations